Communication, culture, and human rights in Africa - Musa, Bala A.; Domatob, Jerry; Hamelink, Cees J., 1940- (Communication, society, and change series ;, 2011)
Communication, Culture, and Human Rights in Africa provides a comprehensive and interdisciplinary analysis of the interface between human rights and civil society, the media, gender, education, religion, health communication, and political processes in sub-Saharan Africa. It weaves theory, history, policy, and case analyses into a holistic intellectual and cultural critique, while offering insightful practical solutions.